2018
DOI: 10.1016/j.maturitas.2018.07.014
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative assessment of health behaviors and experiences during menopause: A cross-sectional, observational study

Abstract: Objectives: A qualitative research study was performed to assess health and lifestyle behaviors of middle-age women during the menopause transition, as well as inform the development of future interventions designed to combat menopause symptoms and improve quality of life during and after menopause. Study Design: Data were collected from 1,611 women via a 21-item questionnaire distributed electronically. Only women who self-reported age ≥40 years and were either peri-menopausal or post-menopausal were includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 30 publications
4
47
1
5
Order By: Relevance
“…Similar results were obtained by other authors where this proportion reached 48%; only 1.8% of the respondents admitted undertaking intensive and regular forms of physical activity [39]. In the study by Marlatt et al [40] among 1,611 peri-and post-menopausal women, those who reported lower exercise frequency (i.e. "rarely" or "occasionally") had a higher modified Kupperman Index score, compared to women who reported higher exercise frequency (i.e.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results were obtained by other authors where this proportion reached 48%; only 1.8% of the respondents admitted undertaking intensive and regular forms of physical activity [39]. In the study by Marlatt et al [40] among 1,611 peri-and post-menopausal women, those who reported lower exercise frequency (i.e. "rarely" or "occasionally") had a higher modified Kupperman Index score, compared to women who reported higher exercise frequency (i.e.…”
Section: Discussionsupporting
confidence: 88%
“…It is important for women to be aware that the quality of their life in the fifth and subsequent decades depends on how much care of health they take. This is also highlighted in other studies [21,40,44].…”
Section: Discussionsupporting
confidence: 77%
“…Self-esteem diminishes and the perception of their own femininity is altered [10,12]. Therefore, engaging in pro-health activities may significantly improve the condition of women in the postmenopausal period and reduce the intensity of experiencing climacteric syndrome symptoms [5,[13][14][15][16]. In order to maintain good health and well-being it is sometimes advisable to modify the lifestyle and certain health behaviours already in the period prior to menopause.…”
Section: Introductionmentioning
confidence: 99%
“…12 Penurunan kualitas hidup terakait masalah kesehatan diakibatkan oleh beberapa gejala menopause tersebut. 13 Gejala psikologis yang dialami pada wanita menopause adalah depresi, mudah marah, cemas, dan perubahan suasana hati. 14 Tabel 1 menunjukkan bahwa sebagian besar responden berusia 51-55 tahun yaitu 26 orang dengan presentase 86,6% dan sisanya berusia 45-50 tahun sebanyak 4 orang dengan presentase 13,3%, sebagian besar responden berpendidikan SMA/sederajat yaitu sebanyak 19 orang dengan presentase 63,3%, pendidikan SD sebanyak 2 orang (6,7%), pendidikan SMP sebanyak 5 orang (16,7%), dan pendidikan S1/diploma sebanyak 4 orang (13,3%), sebagian besar responden tidak bekerja/ibu rumah tangga yaitu sebanyak 27 orang dengan presentase 90% dan sisanya bekekerja sebanyak 3 orang (10%).…”
Section: Pendahuluanunclassified